THE PERFORMANCE OF PHYSIOTHERAPY IN PATIENTS WITH OSTEOSARCOMA AND OTHER ONCOLOGICAL CONDITIONS: AN ANALYSIS OF PAIN INTERVENTION, PALLIATIVE CARE AND SPECIFIC CLINICAL CONTEXTS - Vasconcelos Vieira Siqueira, Viviane; Luís Lopes Gomes de Siqueira, André (Health and Society, 2023)
Physiotherapy plays a fundamental role in the treatment and rehabilitation of cancer patients, especially those diagnosed with osteosarcoma. This narrative review addressed the importance of physiotherapy in various stages of cancer treatment, from diagnosis to post-surgical rehabilitation. Cancer pain, often debilitating, is a major concern, and physiotherapy offers techniques and approaches for its effective management. In palliative care, physiotherapy seeks to alleviate symptoms and improve quality of life, while in post-surgical rehabilitation, the focus is on restoring functionality and promoting the patient’s reintegration. In addition to physical interventions, physiotherapy also addresses the emotional and psychological well-being of patients, offering a holistic approach to cancer care. In short, physiotherapy is essential to improve the quality of life and functionality of cancer patients, addressing physical, emotional and social challenges.